2009
DOI: 10.1371/journal.pntd.0000498
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Sonography: A New Technique to Detect Nerve Damage in Leprosy

Abstract: BackgroundLeprosy is the most common treatable peripheral nerve disorder worldwide with periods of acute neuritis leading to functional impairment of limbs, ulcer formation and stigmatizing deformities. Since the hallmarks of leprosy are nerve enlargement and inflammation, we used high-resolution sonography (US) and color Doppler (CD) imaging to demonstrate nerve enlargement and inflammation.Methology/Principal FindingsWe performed bilateral US of the ulnar (UN), median (MN), lateral popliteal (LP) and posteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
146
3
21

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 126 publications
(208 citation statements)
references
References 14 publications
16
146
3
21
Order By: Relevance
“…The primary finding was that nerves that showed a reversal reaction toward a more intense immune response had a hypervascular pattern, as demonstrated by Doppler studies (or by a marked T2 intensity and increased gadolinium enhancement on MRI). Jain et al (2009), using high-resolution sonography, clearly showed that the kappa value between clinical palpation and the assessment of nerve size by sonography is low. They concluded that clinical examination of enlarged nerves is subjective and inaccurate, whereas sonography provides an objective measure of the nerve dimensions and reveals structural changes over a longer length of the nerve.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The primary finding was that nerves that showed a reversal reaction toward a more intense immune response had a hypervascular pattern, as demonstrated by Doppler studies (or by a marked T2 intensity and increased gadolinium enhancement on MRI). Jain et al (2009), using high-resolution sonography, clearly showed that the kappa value between clinical palpation and the assessment of nerve size by sonography is low. They concluded that clinical examination of enlarged nerves is subjective and inaccurate, whereas sonography provides an objective measure of the nerve dimensions and reveals structural changes over a longer length of the nerve.…”
Section: Discussionmentioning
confidence: 99%
“…Current technological developments leading to improved image quality, reduced US device sizes and reductions in price will make it possible for US to become a tool that can be used in countries in which leprosy is endemic (Jain et al 2009). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In normal nerves there is no detectable blood flow 26. Increased blood flow may be detected in compressive mononeuropathy and inflammatory PN,16 27 possibly reflecting vascular proliferation precipitated by chronic trauma or inflammation (figure 3). …”
Section: Us Features Of Injured Peripheral Nervementioning
confidence: 99%
“…Nerve enlargement and loss of fascicular pattern are seen on US 27 64. These abnormalities are most frequent at common sites of nerve entrapment, in particular the cubital tunnel.…”
Section: Us Findings In Pnmentioning
confidence: 99%